Alumina ceramic microbead green body with high sphericity and method for preparing the same
Patent Information
- Application Number
- CN202410861756.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-06-28
AI Technical Summary
The existing alumina ceramic microspheres have low sphericity, resulting in high wear and easy breakage, making it difficult to meet the grinding requirements of high-purity ultrafine powders.
Alumina ceramic microsphere preforms are prepared by mixing alumina ceramic slurry, dispersant and binder, dripping it onto the surface of a superhydrophobic medium carrier and rolling it under preset vibration conditions, combined with drying treatment.
It improves the sphericity of alumina ceramic microsphere blanks to ≥0.90, enhances wear resistance and strength, and is suitable for grinding media of alumina and aluminum nitride, as well as chromatographic adsorbents, catalyst carriers and other fields.
Smart Images

Figure CN118791287B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of ultrafine grinding media materials technology, and in particular to an alumina ceramic microsphere preform with high sphericity and its preparation method. Background Technology
[0002] Alumina-type abrasive microspheres can serve as grinding media between alumina and aluminum nitride, and can also be used as chromatographic adsorbents, catalysts, or catalyst supports. However, current alumina abrasive microsphere preparation techniques suffer from low sphericity, leading to high wear and breakage. Therefore, research into alumina preform forming and preparation techniques is urgently needed.
[0003] Currently, there are three main molding processes for alumina ceramic microspheres: rolling molding, titration molding, and spray molding. However, the alumina microsphere blanks prepared by these three methods all have problems such as poor sphericity, which makes it difficult to meet the grinding requirements of high-purity ultrafine powders.
[0004] In the current process of forming alumina ceramic microspheres: (1) The rolling forming method includes: first, pre-preparing seed crystals, then using a series of measures such as spraying water mist and adding powder, and then circulating the alumina ceramic slurry repeatedly on the cylinder wall to finally form small balls; the advantage of this method is that it is simple and easy to implement, requires less investment, and can be mass-produced. (2) The drop ball forming method includes: dropping alumina sol into an oil layer (the oil layer usually uses paraffin, mineral oil, etc.), relying on the surface tension of the alumina sol in the oil layer to form spherical sol particles, then gelling the sol particles in an ammonia solution to form gel particles, and finally drying and calcining the gel particles to form spherical alumina; the advantage of this method is that the particle size of the formed small balls is stable, and this method can prepare small balls with a diameter of <1mm. (3) The process of spray granulation includes: first grinding alumina powder into a slurry to obtain alumina slurry, and then spray granulating the alumina slurry with good fluidity at a temperature of 150℃~240℃ to obtain spherical alumina; the advantage of this method is that it can prepare microspheres with a particle size of less than 0.1mm. Summary of the Invention
[0005] This application provides an alumina ceramic microsphere preform with high sphericity and its preparation method to solve the following technical problem: how to improve the sphericity of the alumina microsphere preform.
[0006] In a first aspect, this application provides a method for preparing alumina ceramic microsphere preforms with high sphericity, the method comprising:
[0007] Alumina ceramic slurry, dispersant and binder are mixed to obtain ceramic microsphere blank slurry;
[0008] The ceramic microsphere blank slurry is dripped onto the surface of a carrier with a superhydrophobic medium and rolled under preset vibration conditions to obtain alumina ceramic microsphere green blanks.
[0009] The alumina ceramic microsphere green body is dried to obtain an alumina ceramic microsphere green body;
[0010] The preset vibration conditions include a preset vibration frequency and a preset vibration time, wherein the preset vibration frequency is ≥100 times / min and the preset vibration time is ≥3min.
[0011] Optionally, the preset vibration frequency is 100 times / min to 200 times / min, and the preset vibration time is 3 min to 15 min.
[0012] Optionally, the superhydrophobic medium may include at least one of the following:
[0013] Nanocoatings, nanofibers, superhydrophobic metal materials, and superhydrophobic coatings.
[0014] Optionally, the mass ratio of the dispersant to the alumina ceramic slurry is 1% to 10%.
[0015] Optionally, the dispersant includes at least one of the following:
[0016] Phosphate esters, modified polymer dispersants, and polycarboxylate dispersants.
[0017] Optionally, the mass ratio of the binder to the alumina ceramic slurry is 7% to 15%.
[0018] Optionally, the adhesive aid includes at least one of the following:
[0019] Polyvinyl alcohol, epoxy resin, and acrylic acid.
[0020] Optionally, the solid content of the ceramic microsphere slurry is 60% to 80%.
[0021] Optionally, the drying temperature is 100℃~130℃, and the drying time is ≥7h.
[0022] Secondly, this application provides an alumina ceramic microsphere preform with high sphericity, wherein the alumina ceramic microsphere preform is prepared by the preparation method described in the first aspect, and the sphericity of the alumina ceramic microsphere preform is ≥0.90.
[0023] The technical solutions provided in this application have the following advantages compared with the prior art:
[0024] This application provides a method for preparing alumina ceramic microsphere preforms with high sphericity, comprising: mixing alumina ceramic slurry, a dispersant, and a binder to obtain a ceramic microsphere preform slurry; dropping the ceramic microsphere preform slurry onto the surface of a carrier with a superhydrophobic medium, and simultaneously rolling it under preset vibration conditions to obtain alumina ceramic microsphere green bodies; and drying the alumina ceramic microsphere green bodies to obtain alumina ceramic microsphere preforms; wherein the preset vibration conditions include a preset vibration frequency and a preset vibration time, the preset vibration frequency being ≥100 times / min and the preset vibration time being ≥3min. Mixing alumina ceramic slurry, dispersant, and binder can improve the dispersibility and adhesion of the alumina ceramic slurry, thereby increasing the interfacial tension of the alumina ceramic slurry and obtaining a ceramic microsphere preform slurry with sufficient interfacial tension. Furthermore, preset vibration conditions can include preset vibration frequency and preset vibration time. The preset vibration frequency can be ≥100 times / min, and the preset vibration time can be ≥3min. Based on the "lotus leaf self-cleaning effect" of superhydrophobic media, under the surface force of the superhydrophobic medium, the ceramic microsphere preform slurry with sufficient interfacial tension will continuously roll due to the interaction of interfacial tension and surface force. Combined with vibration, this can promote the formation of uniform spherical droplets in the ceramic microsphere preform slurry. After subsequent drying, these uniform spherical droplets can further promote the formation of uniformly spherical alumina microsphere preforms. Attached Figure Description
[0025] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0026] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 A schematic flowchart illustrating a method for preparing alumina ceramic microsphere preforms with high sphericity, provided in an embodiment of this application;
[0028] Figure 2 A schematic diagram of an alumina ceramic microsphere preform with high sphericity provided in an embodiment of this application;
[0029] Figure 3 The image shows the sphericity test results of an alumina ceramic microsphere preform with high sphericity provided in Embodiment 1 of this application. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0031] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range such as 1, 2, 3, 4, 5, and 6, regardless of the range; in addition, whenever a numerical range is indicated herein, it means including any referenced number (fraction or integer) within the indicated range.
[0032] In this document, terms including "comprising" and the like mean "including but not limited to". "At least one" means one or more, and "more than one" means two or more; "at least one", "at least one of the following", or similar expressions refer to any combination of these items, including any combination of single or multiple items; for example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in this application are commercially available or can be prepared by existing methods.
[0033] Regarding the prior art (1) described in the background art, the inventors found that the disadvantages of this method are low green strength, low compressive strength after firing, poor wear resistance, and difficulty in forming alumina microspheres with a diameter <1mm, making preparation quite difficult. Regarding the prior art (2) described in the background art, the inventors found that the disadvantages of this method are that gel particles are prone to sticking together during the forming process, and the alumina sol microspheres are not easy to separate from the oil phase. Regarding the prior art (3) described in the background art, the inventors found that the disadvantages of this method are that the spray granulation method requires good fluidity of the alumina slurry, which leads to low solid content of the alumina slurry, poor strength of the prepared alumina green, easy breakage after calcination, and the formation of apple-shaped defect microspheres after calcination of the alumina green.
[0034] Figure 1 An exemplary schematic diagram of a method for preparing alumina ceramic microsphere preforms with high sphericity is shown in an embodiment of this application.
[0035] like Figure 1 As shown in the embodiments of this application, a method for preparing alumina ceramic microsphere preforms with high sphericity is provided, the preparation method comprising:
[0036] S1. Mix alumina ceramic slurry, dispersant and binder to obtain ceramic microsphere slurry;
[0037] S2. The ceramic microsphere blank slurry is dripped onto the surface of a carrier with a superhydrophobic medium, and rolled and formed under preset vibration conditions to obtain alumina ceramic microsphere green blanks.
[0038] S3. The alumina ceramic microsphere green body is dried to obtain an alumina ceramic microsphere green body;
[0039] The preset vibration conditions include a preset vibration frequency and a preset vibration time, wherein the preset vibration frequency is ≥100 times / min and the preset vibration time is ≥3min.
[0040] It should be noted that superhydrophobic media are a class of materials that are extremely repellent to water. Superhydrophobic media are usually composed of special micro- and nano-roughened surface structures and low surface energy chemical substances, and their hydrophobic properties are mainly attributed to the micro- and nano-roughened surface structures. Superhydrophobic media generally have a contact angle with water droplets greater than 150°. In addition, the adhesion force between water droplets and the surface of superhydrophobic media is extremely small, resulting in a roll-off angle α of water droplets with superhydrophobic media of less than 10°. The state of a roll-off angle α of water with water of less than 10° is called the "lotus leaf state". Based on the "lotus leaf state" of superhydrophobic media, it can be considered that superhydrophobic media have a "lotus leaf self-cleaning effect". The principle of the "lotus leaf self-cleaning effect" is that there are very complex multiple nano- and micro-scale ultrastructures on the surface of lotus leaves. Under an ultra-high resolution microscope, many tiny papillae can be observed on the surface of lotus leaves. These papillae structures are similar to small hills covering the surface of lotus leaves. These hills are covered with fuzz, and a bun-shaped bunker-like dome can grow on the hill. This bunker-like dome and hill structure allows dust or raindrops to only make contact with a few points on the dome of the "hill" on the leaf surface after falling on the leaf. The raindrops will form a spherical shape under their own tension, which prevents the rainwater from sticking to the lotus leaf, thus causing the raindrops to roll on the surface of the lotus leaf under their own gravity.
[0041] In some optional embodiments, the preset vibration frequency is 100 times / min to 200 times / min, and the preset vibration time is 3 min to 15 min;
[0042] In these embodiments, the preset vibration frequency can be 100 times / min to 200 times / min, and the preset vibration time can be 3 min to 15 min. The preset vibration conditions can be further refined so that the vibration mode, combined with the surface force of the superhydrophobic medium, causes the ceramic microsphere slurry with sufficient interfacial tension to continuously roll on the surface of the hydrophobic medium, thereby causing the ceramic microsphere slurry to form uniform spherical droplets. After subsequent drying, the uniform spherical droplets can cause the ceramic microsphere slurry to form uniform spherical alumina microspheres.
[0043] The preset vibration frequency can be 100 times / min, 110 times / min, 120 times / min, 130 times / min, 140 times / min, 150 times / min, 160 times / min, 170 times / min, 180 times / min, 190 times / min or 200 times / min.
[0044] The preset vibration time can be 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min or 15 min.
[0045] In some alternative embodiments, the superhydrophobic medium includes at least one of the following:
[0046] Nanocoatings, nanofibers, superhydrophobic metallic materials, and superhydrophobic coatings;
[0047] In these embodiments, the types of superhydrophobic media include at least one of nanocoatings, nanofibers, superhydrophobic metallic materials, and superhydrophobic films, which can cover most of the raw materials with superhydrophobic media.
[0048] It should be noted that the nano-coating can be a nanocomposite coating; the superhydrophobic coating can be a superhydrophobic coating prepared from PTEE and fluorinated polyethylene or other fluoropolymers; and the superhydrophobic metal material can be a superhydrophobic metal surface that has undergone special treatment.
[0049] In some optional embodiments, the mass ratio of the dispersant to the alumina ceramic slurry is 1% to 10%.
[0050] In these embodiments, the mass ratio of dispersant to alumina ceramic slurry can be 1% to 10%. The dispersant can be used to effectively improve the dispersion of alumina ceramic slurry, so as to facilitate the bonding between the subsequent binder and alumina ceramic slurry. This can improve the interfacial tension of the ceramic microsphere blank slurry, so as to promote the formation of uniform spherical droplets in the ceramic microsphere blank slurry. After subsequent drying, the uniform spherical droplets can promote the formation of uniform spherical alumina microsphere blanks in the ceramic microsphere blank slurry.
[0051] The mass ratio of the dispersant to the alumina ceramic slurry can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.
[0052] In some alternative embodiments, the dispersant comprises at least one of the following:
[0053] Phosphate ester dispersants, modified polymeric dispersants, and polycarboxylate dispersants;
[0054] In these embodiments, the dispersant includes at least one of phosphate ester dispersants, modified polymeric dispersants, and polycarboxylate dispersants, which can cover most of the dispersants used in alumina ceramic slurries to effectively improve the dispersion of alumina ceramic slurries.
[0055] In some optional embodiments, the mass ratio of the binder to the alumina ceramic slurry is 7% to 15%;
[0056] In these embodiments, the mass ratio of binder to alumina ceramic slurry can be 7% to 15%, which can ensure that the alumina ceramic slurry has a sufficient amount of binder to improve the adhesion of the alumina ceramic slurry, thereby increasing the interfacial tension of the alumina ceramic slurry. This can further promote the formation of uniform spherical droplets in the ceramic microsphere slurry. After subsequent drying, the uniform spherical droplets can promote the formation of uniform spherical alumina microsphere blanks from the ceramic microsphere slurry.
[0057] The mass ratio of the binder to the alumina ceramic slurry can be 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%.
[0058] In some alternative embodiments, the adhesive aid includes at least one of the following:
[0059] Polyvinyl alcohol, epoxy resin, and acrylic acid;
[0060] In these embodiments, the binder includes at least one of polyvinyl alcohol, epoxy resin and acrylic acid, which can cover most binders to effectively improve the adhesion of alumina ceramic slurry, thereby increasing the interfacial tension of the alumina ceramic slurry, which in turn can promote the formation of uniform spherical droplets of ceramic microsphere slurry. After subsequent drying, the uniform spherical droplets can promote the formation of uniform spherical alumina microsphere blanks from the ceramic microsphere slurry.
[0061] In some optional embodiments, the solid content of the ceramic microsphere slurry is 60% to 80%;
[0062] In these embodiments, the solid content of the ceramic microsphere slurry can be 60% to 80%, which can promote the ceramic microsphere slurry to have sufficient alumina solids. Sufficient alumina solids can promote the ceramic microsphere slurry to form uniform spherical droplets. After subsequent drying, the uniform spherical droplets can promote the ceramic microsphere slurry to form uniform spherical alumina microspheres.
[0063] The solid content of the ceramic microsphere preform slurry can be 60%, 65%, 70%, 75%, or 80%.
[0064] It should be noted that different solid contents in the ceramic microsphere slurry can be used to adjust the preset vibration conditions. For example, the preset vibration temperature and preset vibration time can be adjusted in real time according to the solid content of the ceramic microsphere slurry.
[0065] In some optional embodiments, the drying temperature is 100℃~130℃, and the drying time is ≥7h.
[0066] In these embodiments, the drying temperature can be 100℃~130℃ and the drying time can be ≥7h. The drying method can be used to remove the moisture in the alumina ceramic microsphere green body, so as to promote the transformation of the alumina ceramic microsphere green body into alumina microsphere green body with sufficient strength. This can improve the strength of the alumina microsphere green body while promoting the formation of uniform spherical alumina microsphere green body from the ceramic microsphere green body slurry.
[0067] The drying temperature can be 100℃, 105℃, 110℃, 115℃, 120℃, 125℃ or 130℃.
[0068] Figure 2 An exemplary schematic diagram of an alumina ceramic microsphere preform with high sphericity provided in an embodiment of this application is shown;
[0069] Based on a general inventive concept, such as Figure 2 As shown, this application provides an alumina ceramic microsphere preform with high sphericity, which is prepared by the preparation method described above.
[0070] The alumina ceramic microsphere blank is prepared based on the above preparation method. The specific steps of the preparation method can be referred to the above embodiments. Since the alumina ceramic microsphere blank adopts some or all of the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, which will not be repeated here.
[0071] In some optional embodiments, the sphericity of the alumina ceramic microsphere preform is ≥0.90;
[0072] In these embodiments, the sphericity of the alumina ceramic microsphere preform can be ≥0.90, which indicates that the alumina ceramic microsphere preform obtained by the preparation method provided in the embodiments of this application has good sphericity.
[0073] The present application is further illustrated below with reference to specific embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to industry standards; if no corresponding industry standard exists, they are performed according to general international standards, conventional conditions, or conditions recommended by the manufacturer.
[0074] Example 1
[0075] like Figure 1 As shown, a method for preparing alumina ceramic microsphere preforms with high sphericity includes:
[0076] S1. Mix alumina ceramic slurry, dispersant and binder to obtain ceramic microsphere slurry;
[0077] S2. The ceramic microsphere blank slurry is dripped onto the surface of a carrier with a superhydrophobic medium and rolled under preset vibration conditions to obtain alumina ceramic microsphere green blanks.
[0078] S3. Dry the alumina ceramic microsphere green body to obtain the alumina ceramic microsphere green body;
[0079] The preset vibration conditions include a preset vibration frequency and a preset vibration time. The preset vibration frequency is 100 times / min and the preset vibration time is 5min.
[0080] The type of superhydrophobic medium is a Teflon coating nano-coating.
[0081] The mass ratio of dispersant to alumina ceramic slurry is 4%.
[0082] The type of dispersant is polycarboxylic acid ammonium salt dispersant 5027.
[0083] The mass ratio of binder to alumina ceramic slurry is 10%.
[0084] The adhesive is polyvinyl alcohol.
[0085] The solid content of the ceramic microsphere preform slurry is 70%.
[0086] The drying temperature is 100℃ and the drying time is 7 hours.
[0087] Example 2
[0088] Based on the content disclosed in Example 1, the following modifications are made:
[0089] The preset vibration frequency is 100 times / min, and the preset vibration time is 15min.
[0090] The type of superhydrophobic medium is a Teflon coating nano-coating.
[0091] The mass ratio of dispersant to alumina ceramic slurry is 1%.
[0092] The dispersant is polycarboxylate ammonium salt dispersant 5027.
[0093] The mass ratio of binder to alumina ceramic slurry is 7%.
[0094] The adhesive is polyvinyl alcohol.
[0095] The solid content of the ceramic microsphere preform slurry is 60%.
[0096] The drying temperature is 100℃ and the drying time is 7 hours.
[0097] Example 3
[0098] Based on the content disclosed in Example 1, the following modifications are made:
[0099] The preset vibration frequency is 200 times / min, and the preset vibration time is 3 minutes.
[0100] The type of superhydrophobic medium is a Teflon coating nano-coating.
[0101] The mass ratio of dispersant to alumina ceramic slurry is 10%.
[0102] The dispersant is polycarboxylic acid ammonium salt dispersant 5027.
[0103] The mass ratio of binder to alumina ceramic slurry is 15%.
[0104] The adhesive is polyvinyl alcohol.
[0105] The solid content of the ceramic microsphere preform slurry is 80%.
[0106] The drying temperature is 130℃ and the drying time is 7 hours.
[0107] Comparative Example 1
[0108] Based on the content disclosed in Example 1, the following modifications are made:
[0109] Carriers that do not use superhydrophobic media, but directly use ordinary hydrophobic media.
[0110] Comparative Example 2
[0111] Based on the content disclosed in Example 1, the following modifications are made:
[0112] Do not use the preset vibration mode.
[0113] Comparative Example 3
[0114] Based on the content disclosed in Example 1, the following modifications are made:
[0115] The preset vibration frequency is 300 times / min, and the preset vibration time is 20 minutes.
[0116] Comparative Example 4
[0117] Based on the content disclosed in Example 1, the following modifications are made:
[0118] No dispersant is added.
[0119] Comparative Example 5
[0120] Based on the content disclosed in Example 1, the following modifications are made:
[0121] The mass ratio of dispersant to alumina ceramic slurry is 20%.
[0122] Comparative Example 6
[0123] Based on the content disclosed in Example 1, the following modifications are made:
[0124] No adhesive additives are added.
[0125] Comparative Example 7
[0126] Based on the content disclosed in Example 1, the following modifications are made:
[0127] The mass ratio of binder to alumina ceramic slurry is 20%.
[0128] Comparative Example 8
[0129] Based on the content disclosed in Example 1, the following modifications are made:
[0130] The solid content of the ceramic microsphere preform slurry is 40%.
[0131] Comparative Example 9
[0132] Based on the content disclosed in Example 1, the following modifications are made:
[0133] The solid content of the ceramic microsphere preform slurry is 85%.
[0134] Comparative Example 10
[0135] Based on the content disclosed in Example 1, the following modifications are made:
[0136] The drying temperature is 90℃.
[0137] Comparative Example 11
[0138] Based on the content disclosed in Example 1, the following modifications are made:
[0139] The drying temperature is 150℃.
[0140] Relevant experimental and effect data:
[0141] Figure 3 An exemplary diagram showing the sphericity test results of an alumina ceramic microsphere preform with high sphericity provided in Embodiment 1 of this application is illustrated.
[0142] 1. The sphericity of the alumina ceramic microsphere preform obtained in Example 1 was tested, and the results are as follows: Figure 3 As shown, the sphericity of these alumina ceramic microsphere blanks is concentrated at 0.97.
[0143] 2. The sphericity of the alumina ceramic microsphere blanks obtained in each embodiment and comparative example was statistically analyzed, and the results are shown in Table 1.
[0144] Table 1. Sphericity data of alumina ceramic microsphere preforms obtained from various embodiments and comparative examples.
[0145]
[0146] As shown in Table 1, the sphericity of the alumina-based preforms obtained in each embodiment can reach above 0.94. However, in the comparative examples, the excessively long duration and high frequency of vibration used in Comparative Example 3 caused the alumina ceramic microsphere preforms to break, resulting in the inability to obtain complete alumina ceramic microsphere preforms. In Comparative Example 7, the content of the binder was too low at 20%, causing the ceramic microsphere preform slurry to agglomerate and failing to disperse and dissolve, thus preventing the obtaining of complete spherical alumina ceramic microsphere preforms. In Comparative Example 10, the drying temperature was too low, resulting in the alumina ceramic microsphere preforms failing to dry properly, which would affect the subsequent sintering process and prevent the obtaining of complete spherical alumina ceramic microsphere preforms. In contrast, the excessively high drying temperature in Comparative Example 11 affected the internal structure of the alumina ceramic microsphere preforms, hindering the subsequent sintering process and preventing the obtaining of complete spherical alumina ceramic microsphere preforms.
[0147] In summary, the method for preparing alumina ceramic microsphere preforms with high sphericity provided in this application embodiment is based on the "lotus leaf self-cleaning effect" characteristic of superhydrophobic media. Under the surface force of superhydrophobic media, the ceramic microsphere preform slurry with sufficient interfacial tension will continuously roll due to the interaction between interfacial tension and surface force. Combined with vibration, the ceramic microsphere preform slurry can be promoted to form uniform spherical droplets. After subsequent drying, the uniform spherical droplets can promote the ceramic microsphere preform slurry to form uniform spherical alumina microsphere preforms with a sphericity generally above 0.94.
[0148] In addition, although there are various molding methods for alumina ceramic microspheres, more than 90% of the molding methods cannot guarantee that the alumina ceramic microspheres have a high sphericity. However, the method for preparing alumina ceramic microsphere blanks with high sphericity provided in this application has a natural advantage and the prepared alumina ceramic microsphere blanks have a very high sphericity.
[0149] In addition, the embodiments of this application provide a method for preparing alumina ceramic microsphere blanks with high sphericity. This preparation method is simple, has a wide range of applications, and can also provide new ideas for the molding process of all water-soluble inorganic powders.
[0150] Furthermore, the alumina ceramic microsphere preform provided in this application embodiment not only has excellent sphericity, but also has the advantages of high density and low porosity. In addition, the particle size of the alumina ceramic microsphere preform can be uniformly distributed in the range of 0.5mm to 2mm, with a small overall size, and the alumina ceramic microsphere preform has high wear resistance.
[0151] Furthermore, the embodiments of this application provide an alumina ceramic microsphere preform with high sphericity. This alumina ceramic microsphere preform can be mainly used as a grinding medium for alumina and aluminum nitride, and can also be used in the fields of chromatographic adsorbents, catalysts or catalyst supports.
[0152] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed in this application.
Claims
1. A method for preparing alumina ceramic microsphere preforms with high sphericity, characterized in that, The preparation method includes: Alumina ceramic slurry, dispersant and binder are mixed to obtain ceramic microsphere blank slurry; The ceramic microsphere blank slurry is dripped onto the surface of a carrier with a superhydrophobic medium and rolled under preset vibration conditions to obtain alumina ceramic microsphere green blanks. The alumina ceramic microsphere green body is dried to obtain an alumina ceramic microsphere green body, wherein the sphericity of the alumina ceramic microsphere green body is ≥0.90 and the particle size of the alumina ceramic microsphere green body is 0.5mm~2mm; The preset vibration conditions include a preset vibration frequency of 100 times / min to 200 times / min and a preset vibration time of 3 min to 15 min. The mass ratio of the dispersant to the alumina ceramic slurry is 4% to 10%. The mass ratio of the binder to the alumina ceramic slurry is 7% to 15%, and the binder includes at least one of the following: Polyvinyl alcohol, epoxy resin, and acrylic acid; The solid content of the ceramic microsphere preform slurry is 60% to 80%.
2. The preparation method according to claim 1, characterized in that, The superhydrophobic media include at least one of the following: Nanocoatings, nanofibers, superhydrophobic metal materials, and superhydrophobic coatings.
3. The preparation method according to claim 1, characterized in that, The dispersant includes at least one of the following: Phosphate ester dispersants, modified polymer dispersants, and polycarboxylate dispersants.
4. The preparation method according to claim 1, characterized in that, The drying temperature is 100℃~130℃, and the drying time is ≥7h.
5. A preform of alumina ceramic microspheres with high sphericity, characterized in that, The alumina ceramic microsphere preform is prepared by the preparation method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Method for preparing ceramic microspheres by adopting direct titration molding technology
CN112939611A
